UPAYA PENINGKATAN HASIL BELAJAR BIOLOGI MELALUI MODEL PEMBELAJARAN SIMAS ERIC PADA SISWA SMP NEGERI SATU ATAP KAIRATU KABUPATEN MALUKU TENGAH - Mychael Pentury; P M. J Tuapattinaya; S I. A Salmanu (BIOPENDIX, 2019)
Background: The use of appropriate learning models, is an alternative to overcome the problem of students' low absorption of lessons, in order to improve the quality of teaching. SIMAS ERIC learning model (Skimming, Mind Mapping, Questioning, Exploring, Writing, and Communicating) is a learning model that helps teachers train students to plan learning, monitor the learning process, and evaluate student learning outcomes. This study aims to determine the implementation of SIMAS ERIC (Skimming, Mind Mapping, Questioning, Exploring, Writing, and Communicating) learning models to improve biology learning outcomes in eighth grade students of one-roof state junior high school, Kairatu. Method: The research design used was descriptive research. Research subjects were 25 garde VIII students. Data on biology learning outcomes are obtained through pre-test and post-test, observation to observe cognitive, affective, and psychomotor abilities. Results: The average achievement score obtained at the final value is 85.23%. Conclusion: There is an increase in student learning outcomes shown through the results of formative tests after being taught breathing system material in human beings with the application of the SIMAS ERIC learning model (Skimming, Mind mapping, Questioning, Exploring, Writing, Communicating)